Odpowiedzi

2010-03-28T17:24:15+02:00
Rozwiązanie i sprawdzenie w załączniku ;)
2010-03-28T17:31:33+02:00
A) 2x=1-3y
1/2x=2-y/÷½

2x=1-3y
x=1-2


2x=1-3y
x=-1

2×(-1)=1-3y
-2=1-3y
-2-1=-3y
-3=-3y/÷(-3)
1=y

x=-1
y=1
spr.
2x=1-3y
2×(-1)=1-3×1
-2=1-3
-2=-2
L=P

b)x-y-3=0
2x-3y-11=0

x=y+3
2x-3y-11=0

x=y+3
2×(y+3)-3y-11=0

x=y+3
2y+6-3y-11=0

x=y+3
-y=5/×(-1)

x=y+3
y=-5

x=-5+3
x=-2
y=-5
spr.

x-y-3=0
-2-(-5)-3=0
-2+5-3=0
0=0
L=P

c)-3(x+2)+2(x+y)=2
2(y+2)+3(x-y)=-1

-3x-6+2x+2y=2
2y+4+3x-3y=-1

-x+2y=8
3x-y=-5

-x=8-2y/×(-1)
3x-y=-5

x=-8+2y
3x-y=-5

3×(-8+2y)-y=-5
-24+6y-y=-5
5y=-5+24
5y=19/ ÷5
y=3⁴/₅

x=-8+2×¹⁹/₅
x=-8+³⁸/₅
x=-8+7⅗
x=-⅖
spr.
-x+2y=8
-(-⅖)+2×¹⁹/₅=8
⅖+³⁸/₅=8
⁴⁰/₅=8
8=8
L=P